An econometric study of inbound tourism demand in Hong Kong, Macao and Taiwan: A case study of mainland China - Bing Yang (2019)
© Springer Nature Switzerland AG 2019. The purpose of this paper is to estimate tourism demand using quarterly time series data (1998Q1–2017Q4) from Mainland China to Hong Kong, Macao, and Taiwan. Demand functions were used in the Autoregressive Distributive Lag (ARDL) model-Seemingly Unrelated Regression (SUR) model to estimate long-term and short-term tourism demand relationships in Hong Kong, Macao, and Taiwan. The results showed that word-of-mouth effect has a long-term relationship with tourism demand in Hong Kong, Macao, and Taiwan. Tourism price has a significant impact on Macao’s tourism demand for long-term relationship. The seasonality is significant and negative effect in the first quarter. We suggest that launch products suitable for the Spring Festival family tour to attract tourists to travel with their families. We also found that the ARDL-SUR model is more robust than traditional ARDL model in this study.